Long-term permanent deformation behaviour of recycled concrete aggregate with addition of crumb rubber in base and sub-base applications. Issue 121 (June 2019) - Saberian, Mohammad; Li, Jie
Abstract: The structural behaviour of pavements depends on the permanent and resilient deformations. These deformations are accumulated during the pavement lifetime. Although many studies have been done to explore the use of construction and demolition (C&D) waste materials in road pavement construction, the long-term permanent deformation behaviour (i.e., 100, 000 loading cycles) of recycled concrete aggregate (RCA) with an addition of crumb rubber as base/subbase layers has not been studied yet. The aim of this study is to assess whether RCA combined with crumb rubber can be used as the base or sub-base materials or not. Two different crumb rubber sizes were used in this study: a fine type measuring 1–5 mm in diameter and a coarse type measuring 15–20 mm. 0.5, 1% and 2% crumb rubber by weight of the dry aggregate were added to the 20 mm RCA. A series of repeated load triaxial tests were performed to investigate the effects of the sizes and percentages of crumb rubber on the long-term permanent deformation characteristics of RCA incorporating rubber. The results show that only RCA and RCA containing 0.5% fine or coarse rubber can be used as base and sub-base material in pavement in terms of long-term permanent deformation. Highlights: Permanent deformation behaviour of RCA together with rubber were analysed using the repeated load triaxial tests. The number of dynamic loads was considered at 100, 000 load cycles. Two different rubber sizes were used. It was carried out for making a new and green base/subbase applications.